Pengaruh Penerapan Akuntansi Sektor Publik, Good Governance, dan Pengawasan Pengelolaan Keuangan terhadap Pencegahan Fraud - Nurjanah Nurjanah; Istianingsih Sastrodiharjo (Media Ilmiah Akuntansi, 2021)
This research aims to determine the effect of Public Sector Accounting, Good Governance and financial management supervision on Fraud Prevention at the Rawalumbu District Office, Bekasi City. The independent variable consists of Public Sector Accounting, Good Governance, and Financial Management Supervision, and the dependent variable is Fraud Prevention. The sample used was 36 respondents of civil servants at the District Office of Rawalumbu Bekasi. This research is a quantitative research with hypothesis testing using multiple linear regression analysis method. The data used in this study are primary data obtained through distributing questionnaires to several civil servants at the Rawalumbu Bekasi sub-district office. The analysis tool used in this study uses data quality test analysis tools in the form of validity tests and reliability tests as well as hypothesis tests use Multiple Linear Regression. The results of the research show that Public Sector Accounting has a partial effect on Fraud prevention, Good Governance partially has an effect on Fraud Prevention, and financial management supervision has a partial effect on Fraud Prevention at the Rawalumbu District Office, Bekasi City.